Analisis Pengembangan Ekonomi Kreatif dalam Bidang Musik Panting di Kota Banjarmasin - Norminawati (PPJP ULM, 2018)
This study did find out how the strategy of developing a creative economy in the music field of panting in Banjarmasin city and the impact of creative economic development in the music field of panting to panting music player in Banjarmasin city. The study sample is three groups of panting music players in Banjarmasin city consisting of 15 people. Data analysis technique in this study using a descriptive analysis technique and SWOT matrix analysis that is strength, weakness, opportunity, and threat. The SWOT analysis technique used by identifying an internal and external problem in the activity of creative economy development in the music field of panting by minimizing the weakness and maximizing the potency to facilitate the researcher in choosing the right strategy to be used in the development of creative economy in the field of music panting in Banjarmasin city.